OPTIMIZATION OF PREGNANCY MANAGEMENT IN THE CONTEXT OF UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA: A LITERATURE REVIEW (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
The aim of this study is to identify risk factors affecting maternal and fetal health in women with undifferentiated connective tissue dysplasia (UCTD) during pregnancy, to examine associated complications and preventive strategies, and to develop evidence-based, individualized, and multidisciplinary approaches for pregnancy management. The study seeks to provide guidance on preconception planning, disease activity control, safe therapeutic interventions, and optimization of clinical protocols to improve maternal and neonatal outcomes in UCTD patients.